RANCANGAN ALAT BANTU UNTUK MELEPAS DAN MEMASANG MAIN LANDING GEAR DOWNLOCK SPRING BUNGEE PADA PESAWAT BOEING 737-300/400/500 DI PT. AERO NUSANTARA INDONESIA - Ego Widoro; Bambang Sutarmadji; Imam Sarwo Aji (Politeknik Penerbangan Indonesia Curug, 2018)
Process of removal and installation Main Landing Gear downlock Spring Bungee of aircraft Boeing 737 - 300/400/500 at PT. Aero Nusantara Indonesia using a rope as a tool to hold and pull downlock spring bungee. The rope must be pulled with a strong force and requires a minimum two people as well as the processing time of more than four minutes. Another constraint is needed additional pins are mounted on the support shaft uplock holes and the possibility to be separated or broken rope could happen so that it may be accident in its use. The design of this tool consists of four parts, that is a power screw, rod holder, rod player's arm, and frame. Measuring of downlock Spring Bungee dimensions used as a planning and calculation of the design to be created. The calculations results will be used as a design parameter to produce a tool that can be used with just one person and time of use can be speeded up to two minutes as well as lower levels of accidents that may happen.In this design it can be concluded that in general the tools to remove and install the Main Landing Gear downlock Spring Bungee on the Boeing 737-300 / 400/500 is in conformity with the parameters that have been determined so that this design tool can replace previously used and can be done validation can be used in accordance with their purpose